THE ROLE OF SOCIAL MEDIA MARKETING AND PERCEIVED PRICE ON CONSUMER TRUST AND THEIR IMPACT TO REPURCHASE INTENTION IN VIDEO-ON-DEMAND APPS - Yudanto, Daffa Fauzie; Rizan, Mohamad; Rahmi, Rahmi (Universitas PGRI Semarang, 2024)
This research aims to determine the relationship between social media marketing, perceived price, and repurchase intention, as well as the role of customer trust as a moderating variable in the context of the Disney+ Hotstar Video-on-Demand service. The methodology employed for this research is a survey method, utilizing a questionnaire as the data collection instrument. The research sample comprises 280 Disney+ Hotstar users residing in the Greater Jakarta area (Jabodetabek), who follow at least one of Disney+ Hotstar's social media platforms and have subscribed to Disney+ Hotstar within the past year. The sampling technique used in this study is purposive or judgmental sampling. Seven hypotheses were formulated for this research. To test these hypotheses, the Structural Equation Modeling (SEM) method was applied, using SPSS 25 and LISREL 8.8 software. Hypothesis testing indicated positive effects for the following hypotheses: 1) social media marketing on customer trust, 2) social media marketing on repurchase intention, 3) perceived price on customer trust, 4) perceived price on repurchase intention, 5) customer trust on repurchase intention, 6) social media marketing on repurchase intention through customer trust, and 7) perceived price on repurchase intention through customer trust